Envelhecimento e qualidade de vida no trabalho de servidores em abono permanência de uma instituição federal de ensino - Cunha Filho , Carlos Augusto (2020)
Permanence allowance is an important tax relief factor for public social security, since it contributes to the maintenance of active employees, especially those who are in the fullness of their careers, with accumulated knowledge and experience, making them essential for the staff of its operating bodies. In this theme, the study aimed to identify the quality of life in workplace and the motivations of the employees in permanence allowance to remain in the activity even though they are eligible for retirement, in a Federal Educational Institution – IFE. The study is characterized as observational, cross-sectional, providing descriptive information on the prevalence of the analyzed population, carried out in an IFE with multi-campuses, located in the cities of Santa Maria (headquarters), Frederico Westphalen, Palmeira das Missões, Silveira Martins and Cachoeira do Sul, which in october 2019, had 629 public servers in permanence allowance. Secondary data were obtained from the Sistema de Informações para o Ensino – SIE, and the primary data were collected through a structured questionnaire, the first part being composed of socio-demographic information, followed by closed questions according to Walton's WQL model (1973), ending with specific questions related to the actions developed at the IFE, aimed to promote the health of its public servers. The findings showed that the paid public servers in the sample had an average age of 59 years (+4,42), predominantly female (58.5%) married (62.2%), with two children (36.3%), and co-inhabiting the couple and son (45.9%). As for education, the predominance is of PhDs. (31,1%), as well as the 40-hour workweek (48,1%). The health conditions of the respondents are self-declared as excellent (54,8%), with more than half being overweight (51,1%) and diagnosed with dyslipidemia (40,0%), high blood pressure (34,8%) and depression (24,4%), with significant use of medications (68,1%). Regarding lifestyle, it was found that 8.8% are smokers, 55.5% reported consuming alcohol at least once a week, 30.3% adopt occasional walks as physical activity and 54% usually undergo medical assessments annually on their own. For the quality of life conditions in workplace of the sample, the manifestations are mostly satisfied (58,5%), except for the benefits, for which they are dissatisfied (41,4%). With the findings, sociodemographic data, health conditions and lifestyle, reveal important contributions to the improvement of health promotion and prevention actions. The public servers in permanent allowance of the sample were satisfied with their quality of life at work, with the exception of the benefits received. Also, the main motivation for postponing retirement is the taste for the work of the activity developed.